Role of ceftazidime-avibactam on multi-drug resistant and extensively drug resistant gramnegative bacterial isolates (BIRDEM Medical Journal, 2024)
Background: Infections caused by multi-drug resistant (MDR) gram-negative bacteria are becoming very common and now pose a serious public health threat worldwide, as they are difficult to treat due to few treatment options and are associated with high morbidity and mortality. The combination of ceftazidime with the b- lactamase inhibitor avibactam seems to be the right choice in this situation. The aim of the study was to evaluate the in vitro activity of ceftazidime-avibactam and other commonly used antibiotics on MDR and extensively drug resistant (XDR) Enterobacterales and Pseudomonas aeruginosa (P. aeruginosa).Methods: This observational study was conducted in the Department of Microbiology, BIRDEM General Hospital, Dhaka, Bangladesh during January to June, 2022. To report in vitro data for ceftazidime-avibactam on gram-negative isolates a total of 130 (3rd generation cephalosporin resistant) MDR major gram-negative isolates from 65 urine and 65 pus/wound swab samples were taken. Besides, a total of 150 XDR (only colistin sensitive) major gram-negative bacterial isolates from urine and pus/wound swab samples were also taken for this study. Only Esch. coli, Klebsiella sp., P. aeruginosa were included for this study.Results: Esch. coli (79.4%) was most prevailing in urine and P. aeruginosa (97.3%) in pus/wound swab sample. Esch. coli and Klebsiella sp. showed 100% resistance to amoxicillin-clavulunate in urine and pus/wound swab sample. MDR Esch. coli and Klebsiella sp. showed 73.5% and 68% resistance to piperacillin–tazobactum whereas 2.9% and 0.0% to meropenem. A total 9.2% resistance were seen in ceftazidime-avibactum among all MDR major gram-negative isolates and 82.7% ceftazidime-avibactum were resistance to XDR major gram-negative isolates.Conclusion: This analysis presented high susceptibility rates to ceftazidime-avibactam against Enterobacterales strains as well as for MDR phenotype and ESBL phenotype. Ceftazidime- avibactam also achieved the second highest activity result against P. aeruginosa strains including MDR and carbapenem-resistant (CR) phenotypes. These data highlight the need for continued surveillance of antimicrobial activity to treat infections caused by CR phenotypes and for which the options are extremely limited as well as the need for novel antimicrobials.BIRDEM Med J 2024; 14(2): 93-98